مقارنة المعالجة المحاسبية لعمليتي إعادة تامين وقبولات إعادة التامين داخل شركة التامين الجزائرية - منصور منال (جامعة الوادي University Of Eloued, 2024)
تهدف الدراسة لضبط بعض المصطلحات التقنية الخاصة بإعادة التامين وقبولات إعادة التامين، مع مقارنة المعالجة المحاسبية لهاذين العقدين، خلال مرحلتي الإنتاج والحوادث، على ضوء ما جاء به الاشعار رقم 89. تم الاعتماد على المنهج الاستقرائي، حيث تم استخدامه لوصف وضبط بعض المصطلحات التقنية الخاصة بتقنية إعادة التامين والقبولات، تحليل ومقارنة كيفية المعالجة المحاسبية للانتاج والحوادث عند لجوء شركة التامين الى هاتين التقنيتين. وخلصت الدراسة لوجود عدة نقائص وثغرات في كيفية عرض الاشعار رقم 89 لمحاسبة هاتين العمليتين، واكتفائه بتعريفهما دون التفصيل في معالجتها المحاسبية، ما يستدعي المزيد من الضبط والتنسيق وتدارك النقص. The studyaims to control sometech nicaltermsrelat ed to reinsurance and reinsurance acceptances, Comparing the accounting treatment for these two contracts, during the production and accident phases, In light of what was stated in Notice No. 89.We relied on the reconciliation of the descriptive and analytical approach, we used it to describe and control some technical terms related to reinsurance technology and acceptances, Analyze and compare how accounting treats production and accidents when the insurance company resorts to these two techniques. The study concluded that there were several deficiencies and gaps in how Notice No. 89G presented the accounting treatment for these two transactions, He was satisfied with their definition without detailing their accounting treatment, this requires more control and coordination and correcting the deficiency.
Comparing the accounting treatment of two reinsurance transactions and reinsurance acceptances within the Algerian insurance company
Keywords: محاسبة إعادة التامين; محاسبة قبولات إعادة التامين; محاسبة حوادث إعادة التامين; محاسبة حوادث قبولات إعادة التامين; الاشعار رقم 89; Accounting for re -insurance; Accounting for reinsurance acceptances; Accounting for reinsurance; incidents; Accounting of reinsurance acceptance incidents Notice No. 89